## magepker728 3 years ago x^2-6=0 why isnt it (x+2) (x-3)=0 just need to know why

1. hartnn

because 3*3=9 and not 6

2. hartnn

x^2-9 = x^2-3^2 = (x+3)(x-3)

3. hartnn

x^2-6 = x^2-9+3 = (x+3)(x-3)+3

4. magepker728

typo its suppose to be (x-3) (x+2)

5. hartnn

ohh, (x-3)(x+2) = x^2 -3x+2x -6 =x^2 -x -6 and not x^2 -6

6. magepker728

if factored is it (x-3) (x+2) or square root +-6?

7. hartnn

roots are $$\large \pm \sqrt6$$ factors are $$(x+\sqrt6)(x-\sqrt6)$$

8. magepker728

but it is not (x-3) (x+2)

9. hartnn

exatly! its not because (x-3)(x+2) = x^2-x-6

10. magepker728

ooh i see

11. akash809

(x-3) (x-2)= x^2-2x-3x+6=x^2-5x+6...so u got an extra 5x

12. hartnn

13. magepker728

so when ever it is not a perfect square, i have to to take the square root of both side?

14. CliffSedge

You have to take the square root regardless.

15. hartnn

whenever ? when its in the form of x^2 - a^2 = 0

16. hartnn

then shift a^2 to other side and take square root.

17. magepker728

k thanks

18. hartnn

welcome :)

19. febylailani

bcs u hv 1 exttra x :)

20. magepker728

:D